Is Demonstration Effective In Teaching ESP Procedure Text? A Qualitative Study: How to Make a Scrunchie - Roisatul Badriyah; Sri Hartiningsih; Fardini Sabilah (VELES Voices of English Language Education Society, 2023)
Teaching procedural texts in English for Specific Purposes (ESP) can be challenging, often viewed as abstract and unrelated to real-world applications, especially in niche sectors like fashion design. This can hinder English language skill development within such industries. Addressing this, our study evaluates the effectiveness of demonstrations in teaching ESP procedural texts, specifically the crafting of scrunchies. Using a descriptive qualitative method, we identify the merits of demonstrations. Our results show that students not only understand but can also apply the procedural knowledge effectively, as evidenced by their successful creation of scrunchies. Enhanced engagement and participation levels during the learning process further validate the efficacy of the demonstration approach. These insights are pivotal for educators looking to refine their teaching techniques in ESP scenarios that require a balance between theoretical grasp and practical execution.